2005
DOI: 10.1152/ajpregu.00320.2004
|View full text |Cite
|
Sign up to set email alerts
|

Aortic banding in rat as a model to investigate malnutrition associated with heart failure

Abstract: Heart failure is a severe pathology, which has displayed a dramatic increase in the occurrence of patients with chronic heart disease in developed countries, as a result of increases in the population's average age and in survival time. This pathology is associated with severe malnutrition, which worsens the prognosis. Although the cachexia associated with chronic heart failure is a well-known complication, there is no reference animal model of malnutrition related to heart failure. This study was designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
2
8
0
4
Order By: Relevance
“…It is possible that renal blood flow is reduced in mice with suprarenal abdominal aortic banding, resulting in renal dysfunction 30 concomitant with activation of the systemic RAS. 31 It is unlikely that this occurred in the present study because we confirmed that serum creatinine and aldosterone levels were not significantly different between groups and the mean arterial pressure in the AB-4 mice measured from the right femoral artery was above 90 mm Hg, suggesting that the aortic banding procedure did not significantly reduce renal blood flow and impair renal function. Previous studies demonstrated that excess stimulation of cardiopulmonary and arterial baroreceptors impair baroreflex function 32,33 and RAS 32 or Rho-kinase 33 in the brain might contribute to the impaired baroreflex function.…”
Section: Discussionsupporting
confidence: 53%
“…It is possible that renal blood flow is reduced in mice with suprarenal abdominal aortic banding, resulting in renal dysfunction 30 concomitant with activation of the systemic RAS. 31 It is unlikely that this occurred in the present study because we confirmed that serum creatinine and aldosterone levels were not significantly different between groups and the mean arterial pressure in the AB-4 mice measured from the right femoral artery was above 90 mm Hg, suggesting that the aortic banding procedure did not significantly reduce renal blood flow and impair renal function. Previous studies demonstrated that excess stimulation of cardiopulmonary and arterial baroreceptors impair baroreflex function 32,33 and RAS 32 or Rho-kinase 33 in the brain might contribute to the impaired baroreflex function.…”
Section: Discussionsupporting
confidence: 53%
“…A desnutrição proteica implica diversas alterações metabólicas, dentre elas, diminuição significativa de proteínas totais (27,28) , promovendo redução do componente muscular liso da parede vascular e alterando os constituintes da matriz, principalmente o componente elástico (29) . Isso poderia justificar a diminuição na espessura das artérias observada no presente estudo.…”
Section: Discussionunclassified
“…In rat models, it is difficult to noninvasively settle CHF diagnosis, as CHF clinical evidence such as tachypnea and labored respiration can only be subjectively evaluated and requires experience in animal care. Furthermore, body weight (BW) reduction, a commonly found evidence of CHF in clinical and experimental settings (1,15), can be offset by peripheral edema and organ congestion. Other features of CHF usually observed in rats such as pleuropericardial effusion, ascites, thrombi in the left atrium, pulmonary congestion, and right ventricular hypertrophy can only be analyzed after animal euthanasia (3,10).…”
mentioning
confidence: 99%